Systematic review of intervention design and delivery in pragmatic and explanatory surgical randomized clinical trials - Blencowe, NS; Boddy, AP; Harris, A; Hanna, T; Whiting, P; Cook, JA; Blazeby, JM (Wiley, 2015)
Background Surgical interventions are complex, with multiple components that require consideration in trial reporting. This review examines the reporting of details of surgical interventions in randomized clinical trials (RCTs) within the context of explanatory and pragmatic study designs.